Job satisfaction memediasi pengaruh job stress terhadap organizational commitment - Elizabeth Aprilia Mukti Prabawati Priyatno; Dwiarko Nugrohoseno (Universitas Negeri Surabaya, 2026)
This study aims to examine the effect of job stress on organizational commitment with job satisfaction as a mediating variable. The research was motivated by growing concerns over psychological pressure and instability in the textile industry, which may affect employees’ commitment to the organization. Using a quantitative approach, the study collected primary data from 92 production employees through questionnaires and the data analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.2.9. The results show that job stress does not have a significant direct effect on organizational commitment. However, job stress has a significant negative effect on job satisfaction, while job satisfaction has a significant positive effect on organizational commitment. Furthermore, job satisfaction mediates the relationship between job stress and organizational commitment, indicating that employees who experience high job stress tend to report lower job satisfaction, which subsequently reduces their organizational commitment. These findings highlight the important role of job satisfaction in explaining how job stress influences employees’ attitudes toward the organization. This study contributes to the literature by clarifying the mediating mechanism of job satisfaction in the relationship between job stress and organizational commitment within a labor-intensive textile industry context. The results also suggest that organizations should manage work stress and improve job satisfaction to maintain employees’ commitment.